Radiofluorescence of quartz: a review - Schmidt, Christoph; Kreutzer, Sebastian; DeWitt, Regina; Fuchs, Markus (Quaternary geochronology, 2015)
Radiofluorescence (RF) is the luminescence emitted during exposure to ionizing radiation. Charged particles or high-energy photons can be used as stimulation sources, and different designs for measurement equipment have been published. Only few studies have successfully used the quartz RF signal for dosimetry and dating. However, RF is a valuable tool in deciphering charge trafficking in quartz crystals, and also provides information for identifying types of defects causing specific luminescence emissions. Based on models for charge transfer in quartz, RF is seen as resulting from direct recombination of electrons with holes captured in recombination centers (or vice versa) during ionizing irradiation. Competition between reservoir and luminescent centers explains the initial decay of the modeled RF curve followed by a steady rise and also the observed ‘pre-dose’ effect. Emission spectra have been found to be similar to thermoluminescence (TL) spectra, with prevalent emissions in the UV and further emissions for some samples in the blue-green and red range. The high intensity levels and the possibility of choosing longer accumulation times compared to TL and OSL are advantages of RF for spectral measurements. Relative peak intensities in the emission spectra change with dose and absolute intensities with dose rate. Investigating the RF signal with changing measurement temperature allows calculating physical parameters of individual emissions that control thermal quenching. The degree of thermal quenching varies between the emissions, with most intense quenching in the UV. Sensitization of RF by several orders of magnitude has been observed after annealing at 500 °C.
Online verfügbar: 21. Januar 2015
Gesehen am 26.03.2025